Kala azar one of the diseases that play role in autoimmune Thyroid diseases - Haidar J. Muhammed; Majid M. Mahmood; Annie Admon (College of Pharmacy / Mustansiriyah University, 2011)
Autoimmune thyroid diseases (AITD) are disorders of thyroid gland caused by an immune system defect known as autoimmunity. In autoimmunity the immune system errs in its response and targets the body's tissues and cells. To confirm the possible role of Kalaazar disease in complications of autoimmune thyroid diseases (autoimmune thyroglobulin AITG and autoimmune thyroid peroxidase AITPO in this study, 50 patients (male and female) were investigated afflicted with Kalaazar disease, their ages of (< 1-15) years. They were taking from Central Public Health Laboratory .The control group consisted of 25 healthy subjects comparable for age and sex of study groups. The detection of Leishmania donovani parasite test was done by using dipstick rK39, whereas autoimmune thyroid diseases (AITG and AITPO) tests estimated in the same patients by using immunofluorescent method (IFAT). The results indicated that patients were suffering from spleenomagaly, hepatomegaly and decreased in white blood cells and hemoglobin percents. The results of IFAT tests showed that 32 patients were evaluated to have AITD with percent 64 % (AITG and AITPO) of all the subjects enrolled in this study: 40% of the patients have AITG (20 out of 50 patients) and 24% have AITPO (12 out of 50 patients). And the percent of (AITG +AITPO) with accompanying was (11, 22%). The study showed there was a highly significant differences (p<0.01) among patients with AITG, AITPO comparable with other groups. The aim of this study was to detect the effective role of Kalaazar disease in autoimmune thyroid diseases.